E-Torsion Free Acts Over Monoids: Akbar Golchin, Abbas Zare, Hossein Mohammadzadeh - Team, Support (Thai Journal of Mathematics, 2016)
In this paper we introduce E-torsion freeness of acts over monoids, and will give a characterization of monoids by this property of their (cyclic, monocyclic, Rees factor) acts.